Internal Migration flows through Network Analysis: A Comparison between Two Border Regions of Mexico, 1995 and 2015 - LOMELÍ CARRILLO, Uriel; YBAÑEZ ZEPEDA, Elmyra (Frontera Norte, 2017)
This article applies social network analysis methods to recent internal migration studies for two regions in northern Mexico. Using data from 1995 Conteo (Census) and 2015 EIC (Intercensal Survey), the findings reveal that there are significant differences between both regions. In 1995, the northwestern region centrality indicator was more concentrated than for the northeastern region. In 2015, evidence suggests that the net structure in the northeastern region is more concentrated than in the northwestern region.